Study on phosphate solubilizing ability of some bacterial isolates and determination of solubilized phosphorus fractionation in supernatant and microbial biomass - Mitra Ebrahimi; Ali Akbar Safari-sinegani; Mohammadreza Sarikhani; Nasser Aliasgharzad (Biological Journal of Microorganism, 2018)
Introduction:Phosphate solubilizing bacteria play roles in phosphate solubilizing from mineral sources. These bacteria with different mechanisms make it soluble, some parts of solubilized P were absorbed in their biomass and the other parts, released in the soluble form which can be used by other organisms. Materials and methods: In this study, 24 bacterial isolates belonged to different genera such as Azotobacter, Pseudomonas, Rhizobium, Beijerinckia, Klebsiella, Agrobacterium, Alcaligenes, Sphingomnas, Microbacterium and Citrobacter were examined to determine solubilized P from two sources of phosphate (TCP and RP) in Sperber medium. This research was carried out in a complementary random design with three replications. At the end of incubation time, solubilized P in supernatant, amount of P in biomass and total solubilized P were measured. Results: The results showed that isolates are efficient in solubilizing P from TCP than RP. By decreasing pH, solubilized P was increased (r=0.775, p